Recovering from catastrophic disaster in Asia - Waugh, William L.; Han, Ziqiang (Community, environment and disaster risk management ;, 2017)
Volume 18 of the Community, Environment and Disaster Risk Management series looks at how cities and countries recover from catastrophic disasters with a specific focus on Asia. Asia has experienced devastating disasters over the centuries. Proximity to the seismically active Ring of Fire and other plate boundaries, long Pacific and Indian Ocean coastlines, major river and tributary courses, desert and semi-desert areas, and other geographic features create a diversity of hazards and potential hazards. Chapters cover topics including International Humanitarian Assistance and Disaster Recovery, Disaster exceptionalism in India, Immigrant and refugee experiences in Canterbury and Tohoku, Citizen Participation in the Disaster Reconstruction Process after the Great East Japan Earthquake, and Social Capital and Changes in Post-Disaster Recovery Process in China after the 2008 Wenchuan Earthquake.- Resumé vydavatel